Business models in the Asia-Pacific: dynamic balancing of multiple cultures, innovation and value creation. Issue 3 (27th May 2021) - Chin, Tachia; Hu, Qianqian; Rowley, Chris; Wang, Shouyang
ABSTRACT: Owing to the convergence of multiple cultures coupled with the unprecedented rapid development in the decades since the late 1990s, the value creation and innovation logic of Asia-Pacific business models (BMs) has been constantly altered by cultural heterogeneity and thus, have evolved into a more complex and diverse landscape relative to Western developed-economy BMs. Given that relevant issues remain under-researched, the main purpose of our collection is to fill this gap. We provide new insights into identifying, exploring and rationalizing the indigenous innovation ecosystems and unorthodox value-creating logic of BMs emerging from the Greater China territory. Moreover, whereas the COVID-19 crisis has fundamentally changed the way people do business along with the lockdowns followed by some forms of de-globalization; it is expected to see a new wave of BM evolution. We, thus, outline three promising and nascent pathways for future efforts departing from a cultural view to explore the value logic of BMs and BM innovation within the Asia-Pacific region in the post-COVID-19 era: (1) the role of culture in BM innovation; (2) new ways of creating the knowledge and managing knowledge iceberg phenomenon and (3) using the 'Bottom of Pyramid' approach to BM innovation for incorporating social goals into value creation logic.